Phylogenetic relationships of the Fox (Forkhead) gene family in the Bilateria. - Mazet, F; Yu, J; Liberles, D; Holland, L; Shimeld, S (2003)
The Forkhead or Fox gene family encodes putative transcription factors. There are at least four Fox genes in yeast, 16 in Drosophila melanogaster (Dm) and 42 in humans. Recently, vertebrate Fox genes have been classified into 17 groups named FoxA to FoxQ. Here, we extend this analysis to invertebrates, using available sequences from D. melanogaster, Anopheles gambiae (Ag), Caenorhabditis elegans (Ce), the sea squirt Ciona intestinalis (Ci) and amphioxus Branchiostoma floridae (Bf), from which we also cloned several Fox genes. Phylogenetic analyses lend support to the previous overall subclassification of vertebrate genes, but suggest that four subclasses (FoxJ, L, N and Q) could be further subdivided to reflect their relationships to invertebrate genes. We were unable to identify orthologs of Fox subclasses E, H, I, J, M and Q1 in D. melanogaster, A. gambiae or C. elegans, suggesting either considerable loss in ecdysozoans or the evolution of these subclasses in the deuterostome lineage. Our analyses suggest that the common ancestor of protostomes and deuterostomes had a minimum complement of 14 Fox genes.